2010
DOI: 10.1007/978-3-642-11805-0_5
|View full text |Cite
|
Sign up to set email alerts
|

On the Perspectives Opened by Right Angle Crossing Drawings

Abstract: Abstract. Right Angle Crossing (RAC) drawings are polyline drawings where each crossing forms four right angles. RAC drawings have been introduced because cognitive experiments provided evidence that increasing the number of crossings does not decrease the readability of the drawing if the edges cross at right angles. We investigate to what extent RAC drawings can help in overcoming the limitations of widely adopted planar graph drawing conventions, providing both positive and negative results. First, we prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Angelini edge [1]. A relaxation of RAC drawings, called large angle crossing drawings (drawings where crossings form angles of at most α, for some fixed constant 0 < α < π 2 ) has been studied by several authors: Di Giacomo et al proved bounds and trade-offs on the area requirement and number of bends of large angle crossing drawings [2], and Dujmović et al showed bounds on the number of edges in straight-line large angle crossing drawings [4].…”
Section: Theoremmentioning
confidence: 99%
“…Angelini edge [1]. A relaxation of RAC drawings, called large angle crossing drawings (drawings where crossings form angles of at most α, for some fixed constant 0 < α < π 2 ) has been studied by several authors: Di Giacomo et al proved bounds and trade-offs on the area requirement and number of bends of large angle crossing drawings [2], and Dujmović et al showed bounds on the number of edges in straight-line large angle crossing drawings [4].…”
Section: Theoremmentioning
confidence: 99%
“…Recently, Angelini et al [6] considered some special cases for drawing RAC graphs, for example, acyclic planar RAC digraphs and upward RAC digraphs. They showed that there exist acyclic planar digraphs not admitting any straight-line upward RAC drawing and that the corresponding decision problem is NP-hard.…”
Section: Previous Workmentioning
confidence: 99%
“…Two main kinds of drawings have been considered: Drawings with crossing angle resolution π 2 (the largest possible value), called Right Angle Crossing drawings (or RAC drawings) (see, e.g., [2,4,5,8,10,11,13,18]), and drawings whose crossing angle resolution is at least a given α ∈ (0, π 2 ) (see, e.g., [1,7,9,12]). …”
Section: Introductionmentioning
confidence: 99%